2015
DOI: 10.7183/0002-7316.80.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Caves and Rockshelters in the Hunter-Gatherer Taskscape of the Archaic Midsouth

Abstract: This paper evaluates previous models of cave and rockshelter use in the American Midsouth from the Early to the Middle Archaic periods. Four sites are compared in order to identify variability in activities, seasonality, occupation intensity, and function. Focus is placed on using the often overlooked feature assemblages to discern these activities. Data suggest that the changing use of many caves and rockshelters is not one of longer term occupation as base camps, as has been previously argued, but rather as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In proportional symbol maps [CL06], the size of the symbols is also used to encode information about the sites. Symbol maps may represent the geological distribution of lithics sources in the research area [Mor15], site assemblages or occupation histories [GF15, Bri11], or the spatial distribution of features within a site [HM15], to name but a few examples. The problem with this approach is always the same: if sites or features are close to each other, the symbols will overlap.…”
Section: Introductionmentioning
confidence: 99%
“…In proportional symbol maps [CL06], the size of the symbols is also used to encode information about the sites. Symbol maps may represent the geological distribution of lithics sources in the research area [Mor15], site assemblages or occupation histories [GF15, Bri11], or the spatial distribution of features within a site [HM15], to name but a few examples. The problem with this approach is always the same: if sites or features are close to each other, the symbols will overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Excellent examples of case studies challenging restricted interpretive paradigms can be found in the Midwest (Diaz-Granados et al 2015;Pedde and Prufer 2001;Stelle 2012;Wagner 2004), Southeast (Claassen 2009(Claassen , 2011Claassen and Compton 2011;Crothers 2012;Homsey-Messer 2015;Prufer and Prufer 2012;Sabo III et al 2012;Salzer and Rajnovich 2001;Simek et al 2012Simek et al , 2013, Southwest (Nicolay 2012), Mesoamerica (Heyden 2005;Moyes and Brady 2012;Rissolo 2005), and the Caribbean (Lace 2012).…”
Section: Overview Of Theoretical Framework In Cave and Rockshelter Smentioning
confidence: 99%
“…This approach often results in mutually exclusive categories of utilitarian or ritual function, which undermines the fluidity of hunter-gatherer uses of landscapes. Recent scholarship is beginning to revisit this discussion to argue that caves and rockshelters are highly dynamic settings that do not easily fit into one category or the other, but rather served a range of purposes that deserve sincere reconsideration (Claassen 2011(Claassen , 2012(Claassen , 2015Crothers 2012;Homsey-Messer 2015;Moyes 2012;Walker 2010). It is this documented variation that requires more critical engagement that goes beyond static interpretive categories.…”
Section: Introductionmentioning
confidence: 99%